Bacterial assemblages on eggs reflect nesting strategies in wetland-associated birds - Wouter F. D. van Dongen; Hanja B. Brandl; Alžbeta Darolová; Ján Krištofík; Herbert Hoi (PLoS ONE, 2025)
Birds host diverse bacterial assemblages, which play a critical role in individual health, but which can also lead to disease or mortality. It is therefore important for developing embryos to acquire appropriate bacterial communities from maternal (vertical transmission) and environmental (horizontal transmission) sources. Eggshell bacterial assemblages are acquired before and after oviposition, and are shaped by external factors, including habitat, nesting material and parental incubation. Understanding the source of eggshell bacteria is important, because eggshell penetration of horizontally-transmitted bacteria can affect embryonic health. Most research on eggshell-associated bacteria has occurred on ‘dry-nesting’ terrestrial birds. However, little is known on bacterial acquisition in waterbirds, particularly in nests where eggs are in direct contact with water. Moist environments favour bacterial growth and wet-nesting species are therefore expected to have higher bacterial loads. To date, no study has focussed on contrasting the abundance and diversity of eggshell bacterial assemblages in wet- and dry-nesting species. We used both bacterial culture and genetic techniques (automated ribosomal intergenic spacer analysis) to document the bacterial load and assemblage structure of eggshell-associated bacteria in both wet- and dry-nesting wetland-associated bird species. Bacterial loads were several orders of magnitude greater on eggs of wet-nesting species and bacterial assemblages tended to cluster by nesting strategy. These findings suggest a possible association of eggshell-associated bacteria with nesting strategies in these species. Further research is, however, required to confirm these patterns, incorporating more comprehensive sampling and utilising more advanced genetic approaches. Overall, our findings highlight a promising direction for future research into the association between nesting in moist environments and eggshell-associated bacteria, as well as the potential for antimicrobial adaptations that may characterise the eggshells of these species.